Preoperative Preparation of patients with Coronary Heart Disease Before Non-Cardiac Surgery - Fiona C. Caldwell, Ava M. Davis, Elijah M. Mitchell (Academic Journal of Clinicians, 2024)
Objective: This study aimed to review the preoperative preparation strategies for patients with coronary heart disease (CHD) undergoing non-cardiac surgery, focusing on optimizing perioperative outcomes and reducing cardiac complications. Methods: A review was conducted to identify studies and guidelines related to the preoperative management of patients with CHD before non-cardiac surgery. Key points including risk assessment, medical optimization, pharmacological interventions, and perioperative monitoring were analyzed. Results: Preoperative preparation of patients with CHD involves a multifaceted approach. Risk assessment tools, such as the Revised Cardiac Risk Index (RCRI) and the American College of Cardiology/American Heart Association (ACC/AHA) guidelines, aid in stratifying patients' cardiac risk. Medical optimization may include optimizing blood pressure control, managing antiplatelet and anticoagulant medications, and ensuring adequate glycemic control. Pharmacological interventions such as beta-blockers and statins may be utilized when indicated. Perioperative monitoring, including electrocardiography and troponin measurement, helps detect myocardial ischemia or infarction. Conclusion: Preoperative preparation plays a vital role in reducing cardiac complications in patients with CHD undergoing non-cardiac surgery. Individualized risk assessment, medical optimization, and careful perioperative monitoring are crucial in optimizing outcomes. Collaboration among cardiologists, anesthesiologists, and surgeons is essential for comprehensive preoperative management.